Synoptyczne uwarunkowania intensywnych opadów śniegu w wybranych regionach Europy = Synoptic conditions underpinning intensive snowfalls in selected regions of Europe - Tomczyk, Arkadiusz Marek; Bednorz, Ewa (IGiPZ PAN, 2014)
The aim of the work described here has been to determine synoptic situations associated with intensive snowfalls in selected regions of Europe. Specifi cally, an analysis was carried out for three stations representing regions with different climatic conditions in winter. Synoptic conditions were characterized on the basis of atmospheric pressure at sea level, the height of the 500 hPa isobaric area and air temperature at the 850 hPa isobaric level. Typical features of synoptic situations leading to intensive snowfalls in Belgrade are negative SLP anomalies and a lowering height of the 500 hPa isobaric area over SouthernEurope, as indicating the presence of a low-pressure system. Heavy snowfalls in Suwałki, Poland, are in turn associated with the occurence of a low-pressure system centred on the south-eastern Baltic Sea. Finally, the occasional snowstorms characterising Ubachsberg in The Netherlands are associated with extensive low-pressure troughs that bring in humid and cold air masses from the north and north-west.
24 cm
Keywords: Europe; snow cover; circulation; synoptic conditions